2018
DOI: 10.1080/14712598.2018.1458089
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of rheumatology biosimilars in the absence of forced switching

Abstract: Background: To describe the uptake and system-level effects of the introduction of biosimilars in a setting without forced switching. Research design and methods:We used data from the Swedish Rheumatology Quality register from start of marketing of infliximab (Remsima® and Inflectra®) and etanercept (Benepali®) biosimilars until December 31 st 2016. We compared users of each originator-product and its biosimilar(s) by line of treatment: bDMARD-naïve patients, non-medical switchers (vs. matched patients remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…In Denmark, it was mandatory to switch all patients treated with INF or ETN to their respective biosimilars, when the biosimilars were marketed 9 14 20. In Sweden, the strategies for both new starts and switching differed across the different counties,19 and in Finland, INF or a biosimilar was used based on exclusive pricing negotiations made in individual hospital districts, whereas the first etanercept biosimilar was not reimbursed in Finland until January 2018. In Iceland, the least expensive bDMARDs are recommended as first-line drugs based on an annual tendering process under the authority of the Icelandic Health Insurance (state insurance company).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Denmark, it was mandatory to switch all patients treated with INF or ETN to their respective biosimilars, when the biosimilars were marketed 9 14 20. In Sweden, the strategies for both new starts and switching differed across the different counties,19 and in Finland, INF or a biosimilar was used based on exclusive pricing negotiations made in individual hospital districts, whereas the first etanercept biosimilar was not reimbursed in Finland until January 2018. In Iceland, the least expensive bDMARDs are recommended as first-line drugs based on an annual tendering process under the authority of the Icelandic Health Insurance (state insurance company).…”
Section: Methodsmentioning
confidence: 99%
“…In the Nordic region (Denmark, Iceland, Finland, Norway and Sweden), the strategies for transition have differed markedly across the countries, depending primarily on differences in pricing 18. Within Sweden, the uptake was further diversified by separate tender processes in different counties 19. As a result, during the period 2014–2017, biologics-naïve patients with SpA in the Nordic countries have started both originator and biosimilar versions of infliximab and of etanercept.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, patent expiration and the resultant loss of market exclusivity has facilitated the introduction of biosimilar agents based on the anti-TNF biologic agents etanercept, infliximab and, most recently in October 2018, adalimumab, to clinical care (18)(19)(20). Rheumatology data from Sweden, where switching to biosimilars is not mandatory, show that when the etanercept and infliximab reference products went off patent, there was an increase in the overall use of biologic treatment, suggesting that biosimilars were not only replacing the reference products, but were increasing the overall rate of biologic therapy initiation (21). This finding reflects the favorable cost differential of the anti-TNF biosimilars (21).…”
Section: Treatment Accessibilitymentioning
confidence: 99%
“…Rheumatology data from Sweden, where switching to biosimilars is not mandatory, show that when the etanercept and infliximab reference products went off patent, there was an increase in the overall use of biologic treatment, suggesting that biosimilars were not only replacing the reference products, but were increasing the overall rate of biologic therapy initiation (21). This finding reflects the favorable cost differential of the anti-TNF biosimilars (21). The recent introduction of adalimumab biosimilars to the European market provides further opportunity to improve cost savings and facilitate access to effective biologic therapy (1,18,20).…”
Section: Treatment Accessibilitymentioning
confidence: 99%
“…In Asia, biosimilar use within the first year was greater than 10% . A study in Sweden showed that the uptake of biosimilars was over 30% by the end of 2016 . There are various plausible reasons for the low uptake of biosimilars in the United States.…”
Section: Discussionmentioning
confidence: 99%